WC-5Co Cemented Carbides Fabricated by SPS - P. Siwak; D. Garbiec (Archives of Metallurgy and Materials, 2018)
New graphite tools were designed and produced to fabricate a semi-finished product from which nine cutting inserts were obtained in one spark plasma sintering process. As a result, WC-5Co cemented carbides were spark plasma sintered and the effect of various sintering parameters such as compacting pressure, heating rate and holding time on the main mechanical properties were investigated. It was shown that WC-5Co cemented carbides spark plasma sintered at 1200°C, 80 MPa, 400°C/min, for 5 min are characterized by the best relation of hardness (1861 ±10 HV30) and fracture toughness (9.30 MPa·m1/2). The microstructure of these materials besides the WC ceramic phase and Co binder phase consists of a synthesized Co3W3C complex phase. Comparison with a commercial WC-6Co cutting insert fabricated by conventional powder metallurgy techniques shows that spark plasma sintering is a very effective technique to produce materials characterized by improved mechanical properties.